Specimen Level and Component Level Simulations of Fatigue Crack Growth Behavior under Cyclic Bending - R. Suresh Kumar; S. Jalaldeen (Fracture and Structural Integrity)
This paper describes a benchmark analysis that was performed to demonstrate numerical simulation capability on fatigue crack growth (FCG) behaviour under cyclic bending. Economic design of a piping system against the leak-before-break (LBB) criteria require an accurate estimate of crack growth behaviour. To this end, two representative geometries were selected. The first model was a plate-type geometry with a specimen-type feature, and the other model was a prototype pipe bend geometry with the component feature. The numerically simulated FCG behaviour was found to agree with published data within engineering accuracy for both the specimen-level and the component-level geometries. Details of the FCG simulation, its validation against benchmark data, and plausible reasons the difference observed in the FCG behaviour of the specimen-level and full-scale component-level geometries are presented in this paper. The results of the FCG simulation strengthen the argument for performing component-level FCG simulation for an accurate demonstration of LBB for the power plant piping systems.